AKTUALISASI TQM DALAM MENINGKATKAN PROFESIONALISME GURU DI LEMBAGA PENDIDIKAN ISLAM - Mufidah, Luk-luk Nur (STAIN Pamekasan, 2009)
Abstrak: Teacher have duty instruct and guide pupils to be progressively mount its knowledge, skilled progressively its skill and constructive progressively and expand its potency. In executing its duty, teacher have to show the existence of technical skilled which supported by certain personality attitude because based on by guidances of special behaviour (code of etik) firming up them in one profession corps. The Teacher profession have to be supported with high professionalism in realizing mission and vision an education institute to be created quality of good grad and responsibility learn. To obtain high teacher professionalism utilize to realize quality of grad which is good to be, needed is Total of Quality Managemet (TQM) as a means of to reach the target which flange to continous improvement quality, satisfaction costumer and assurance quality.